NON-LINEAR OPTICAL PROPERTIES STUDY OF TWO HETEROCYCLIC COMPOUNDS: Life Sciences-Chemistry - V.T. MUTTANNAVAR; RAVEENDRA. MELAVANKI; P. BHAVYA; RAVIRAJ KUSANUR; N. R. PATIL; L. R. NAIK (International Journal of Life Science and Pharma Research, 2022)
In an attempt towards understanding the relation between molecular structure-nonlinear optic activity (NLO) among heterocycles, with special reference to the identity, number and position of the heteroatom, semiempirical calculations were carried out. This paper reports the Non-linear optical properties of two heterocyclic compounds namely 3-[2-Oxo-2-(2-oxo-2H-chromen-3-yl)-ethylidene]-1,3-dihydro-indol-2-one (3OCEDI) and Quinolin-8-ol (QL). To understand the Non-Linear Optical properties of coumarin dyes we computed dipole moment (μ), electronic polarizability (α), and the mean was first hyperpolarizability (βo) using B3LYP density functional theory method in conjunction with 6-31G(d, p) basis set.All the calculations were carried out in gas phase and in acetonitrile medium. The optimized geometry of both compounds shows a 3D helical structure. The results indicate that given the same number and type of atoms and double bonds in a molecule, linear conjugation excels over cyclic or crossed conjugation in enhancing hyperpolarizabilities and it seems to be far more critical than a chiral centre.